ENHANCES PERFORMANCE OF REAL-TIME KWH METER BASED ON IOT AND ESP-32 MICROCONTROLLE - Miranda Adelina Hutabarat; Solly Aryza; Dicky Lesmana (Jurnal Scientia, 2023)
At the momentIn Indonesia, the process for checking postpaid electricity meters is carried out by PLN officers by taking a photo of the KwH electricity meter stand. Officers will come to the house then check and take photos of the meter to ensure the electricity bill matches the customer's usage. This is less efficient because it wastes a lot of time and energy. For this reason, a system was created that can monitor electricity usage in real time through the Firebase application and MIT App Invertor so that the monitoring process can run quickly and accurately. This system uses ESP32 as a microcontroller, Arduino as a sender of data reading results, PZEEM 004-T as an electrical data reader, SIM 800 v2 module as a data sender to Android and LCD to display data.